ANALISIS KESALAHAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL MATEMATIKA MATERI OPERASI MATRIKS - Verencia Oroh; Ontang Manurung; Nicky K. Tumalun (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to find out what mistakes students make when solving addition, subtraction, and matrix multiplication problems. The method in this study is a qualitative descriptive research method. Collection data are using evaluations and interviews. This study was followed by 25 people from class XI SMA Negeri 1 Langowan. This study concluded that: (1) Many students experienced errors, there were some students who answered correctly, some did not answer and there were also wrong facts, concepts, principles, and operations, (2) Based on the results of evaluations and interviews, there are mistakes made by class XI students at SMA Negeri 1 Langowan in solving matrix operation problems: Fact errors, namely: errors related to the material in the questions; Conceptual errors are errors in understanding abstract ideas; Errors in principle, namely: errors in applying the principles that exist in the problem; Operational errors, namely errors in mathematical calculations, (3) conceptual errors occurred in 12 students. As was done with the absent student number 24, this student operated the addition of a row by column matrix, (4) factual errors occurred in 2 students, conceptual errors occurred in 23 students, and operation errors occurred in 4 students. One of the errors in question number 2 was taken, as did the absent student number 8 making a factual error, (5) factual error occurred in 2 students, and operating error occurred in 5 students. One of the errors in question number 3 was taken, as did student absentee number 20 making an operation error, (6) factual error occurred in 4 students, a conceptual error occurred in 1 student, principle error in 6 students, and operator error. on 2 students. One of the errors in question number 4 was taken, as did the absent student number 15 making a principle error, (7) the proportion of errors from each question based on a predetermined error category, namely, factual error, concept error, principle error, operating error, ( 8) The average percentage of errors of all students in solving matrix operation problems are: (a) 5.85% factual error, (b) 43.67% conceptual error, (c) 10% principle error, (d) Operational error 12.69%.